(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
In this work the use of natural magnetite in coast sand of Wadi-kandil area in Syria in removal of Methylene Blue (MB) from aqueous solution was studied. The XRD measurements showed that the sample contents the crystalline magnetite and another compounds. The magnetite in the simple was separated using magnetic method and the percentage of magnetite in the sample about 70 %. After separating the magnetite was used to removal the MB from aqueous solution at different initial concentration of MB (5 , 10 , 20 , 40 , 60 mg/l ) and using different dosage of magnetite (0.2 , 0.5 , 1 g) at different values of pH and temperature 25° C. The adsorption of MB increasing by increasing initial concentration of MB and decreasing by increasing of pH value and the removal of MB was clearly increased when the dosage of magnetite was increased , the removal values were 47.8% , 84.9% , 88.7% for magnetite dosage (0.2 , 0.5 , 1 g) respectively at concentration 5 mg/l of MB . While the adsorbed amount of MB per mass unit of magnetite was decreased because the adsorption sites weren’t saturated. The Treatment of adsorption data according Lngmuere and Frenglish models showed that the adsorption process accrued on the energetic homogeneous and heterogeneous sites. تمت في هذا العمل دراسة استخدام الماغنتيت الطبيعي في الرمال الشاطئية لمنطقة وادي قنديل في سوريا في عملية إزالة أزرق المتيلين من محاليله المائية . بينت قياسات الأشعة السينية XRD أن العينة من الرمل الشاطئي تحوي الماغنتيت المتبلور بشكل جيد بالإضافة إلى بعض المركبات الأخرى , وتم فصل الماغنتيت بالطريقة المغناطيسية وتبين أن نسبته في الرمال الشاطئية المدروسة تشكل حوالي %70 . استخدم الماغنتيت بعد فصله في عملية إزالة MB من محاليله المائية وذلك عند تراكيز ابتدائية مختلفة لـ MB(5 , 10 , 20 , 40 ,60 mg/l ) وذلك باستخدام جرعات مختلفة من الماغنتيت (0.2 , 0.5 , 1 g)عند قيم pH مختلفة ودرجة حرارة 25°C, وتبين أن إمتزاز أزرق المتيلين يزداد بازدياد التركيز الابتدائي ويتناقص بازدياد قيمة pH الوسط, كما تبين أن نسبة إزالة MB تزداد بشكل واضح بازدياد كمية الماغنتيت المستخدم , وكانت نسبة الإزالة 47.8% , 84.9% , 88.7% وذلك من أجل جرعة من الماغنتيت 0.2 , 0.5 ,1g على الترتيب عند تركيز معين لـ MB يساوي 5 mg/l بينما تتناقص كمية MB الممتزة بالنسبة لواحدة الكتلة من الماغنتيت وذلك لعدم حصول إشباع للمراكز الامتزازية . تبين من خلال معالجة البيانات الامتزازية وفق نموذجي لانغموير و فرندلش أن عملية امتزاز MB تحدث على المراكز المتجانسة الطاقة وفق نموذج لانغموير وبشكل تنافسي على المراكز غير المتجانسة طاقياً وفق نموذج فرندلش.